Genome-wide analysis and identification of stress-responsive genes of the CCCH zinc finger family in Capsicum annuum L. - Tang, Wenchen; Hao, Yupeng; Ma, Xinyu; Shi, Yiqi; Dang, Yongmeng; Dong, Zeyu; Zhao, Yongyan; Zhao, Tianlun; Zhu, Shuijin; Zhang, Zhiyuan; Gu, Fenglin; Liu, Ziji; et al. (Frontiers in Plant Science, 2023)
The CCCH zinc finger gene family encodes a class of proteins that can bind to both DNA and RNA, and an increasing number of studies have demonstrated that the CCCH gene family plays a key role in growth and development and responses to environmental stress. Here, we identified 57 CCCH genes in the pepper (Capsicum annuum L.) genome and explored the evolution and function of the CCCH gene family in C. annuum. Substantial variation was observed in the structure of these CCCH genes, and the number of exons ranged from one to fourteen. Analysis of gene duplication events revealed that segmental duplication was the main driver of gene expansion in the CCCH gene family in pepper. We found that the expression of CCCH genes was significantly up-regulated during the response to biotic and abiotic stress, especially cold and heat stress, indicating that CCCH genes play key roles in stress responses. Our results provide new information on CCCH genes in pepper and will aid future studies of the evolution, inheritance, and function of CCCH zinc finger genes in pepper.